An autopsy case of infective aortic aneurysm with Pasteurella multocida infection: clinicopathological appearance and a review of literatures - Kazuhiro Nomoto; Yukiko Hata; Shojiro Ichimata; Syu Mizuno; Naoki Nishida (BMC, 2023)
Abstract Here, we showed our clinicopathological findings of infected aortic aneurysm (IAA) with Pasteurella multocida, which is a Gram-negative coccobacillus and is part of the normal oral flora of many animals. The patient was a 76-year-old male animal owner with a history of diabetes mellitus, alcoholic liver damage, and laryngeal cancer. He died 16 days after admission without undergoing operation because of poor general condition. Autopsy showed saccular outpouching with loss of the existing aortic wall and marked neutrophilic infiltration in the suprarenal abdominal aorta. Rupture was not evident. A polymerase chain reaction assay using DNA extracted from formalin-fixed paraffin-embedded specimen of the aneurysmal wall detected the Pasteurella multocida gene, therefore we conclude that the present case was IAA of native aorta with Pasteurella multocida infection. A review of the literature showed that IAA of native aorta with Pasteurella multocida infection is opportunistic and that liver disorder, alcohol addiction, diabetes mellitus, and animal bite may increase its risk. On the other hand, aortic endograft infection with Pasteurella multocida frequently occurred without an immunocompromised state. Pasteurella multocida may be a distinct causative microorganism in IAA, and/or sepsis when the participant is an animal owner.